Solusi Tindak Pelecehan Seksual terhadap Kaum Perempuan: Studi Takhrij dan Syarah Hadis - Linda Winingsih; Hidayatul Fikra; Dian Siti Nurjanah (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith regarding sexual harassment through the application of takhrij and syarah hadith studies. This research method uses a qualitative approach through literature study related to contemporary analysis. The results of this study found that this hadith about sexual harassment is authentic in terms of sanad and matan. The discussion of this research is that the Messenger of Allah greatly appreciated women by not touching women who were not their mahrams, even during baiat. The conclusion of this study is that sexual harassment is an act that is contrary to what has been taught by the Prophet through his sunnah, so that several solutions to the crime of sexual harassment were found in this study, namely sex education, fostering courage, protection, law enforcement, complaint booths, reporting ethics, empathy, and healing therapy for traumatic effects. This research is expected to provide benefits and prevent sexual harassment. This study has shortcomings and limitations so that further research is recommended by reviewing the meaning of hadith from various perspectives of disciplines.